MORAL-VOLUME READINESS OF A CHILD TO STUDY AT SCHOOL (Conferencea, 2024)
This article discusses the moral-volitional readiness of a child to study at school and the development of moral behavior, will, moral emotions and consciousness, which allows him to actively acquire a new social perspective, as well as his relationships with his teacher and classmates.